Analysis of trusted execution environment usage in Samsung KNOX - Atamli-Reineh, A; Borgaonkar, R; Balisane, R; Petracca, G; Martin, A (Association for Computing Machinery, 2016)
Mobile systems have become widely adopted by users to perform sensitive operations ranging from on-line payments for personal use to remote access to enterprise assets. Thus, attacks on mobile devices can cause significant loss to user's personal data as well as to valuable enterprise assets. In order to mitigate risks arising from attacks, various approaches have been proposed including the use of Trusted Execution Environment (TEE) to isolate and protect the execution of sensitive code from the rest of the system, e.g. applications and other software.However, users remain at risk of exploits via several types of software vulnerabilities - indicating that enterprises have failed to deliver the required protection, despite the use of existing isolation technologies. In this paper, we investigate Samsung KNOX and its usage of TEE as being the current technology providing secure containers. First, we study how KNOX uses TEE and perform analysis on its design consideration from a system vulnerabilities perspective. Second, we analyse and discuss recent attacks on KNOX and how those attacks exploit system vulnerabilities. Finally, we present new shortcomings emerging from our analysis of KNOX architecture. Our research exhibits that system vulnerabilities are the underlying cause of many attacks on systems and it reveals how they affect fundamental design security principles when the full potential of TEE is not exploited.